LEADERSHIP PRINCIPLES AND PURPOSE developing leadership effectiveness and future-focused... capability. - Sharpley, David ([S.l.] : PRODUCTIVITY PRESS, 2024)
This book provides a fresh perspective on leadership and the steps required to achieve high performance. It explores how we create purpose by moving from vision and values through principles to action.
Chapter 10: Module 1: Elements of High Performance -- The Importance of Feedback -- Build on Feedback -- Listen to the Feedback -- Clarify the Information -- Explore the Alternatives -- Develop an Action Plan -- Understanding Your Personal Style -- Fast-Track Leadership Development -- Chapter 11: Module 2: Effectiveness at Work -- Do You Always Use the Best Approach? -- Reflection and Forward Planning -- Sample Competency: 'Executes the Strategy' (Focus on Delivery) -- Sample Competency: Developing Capability -- Sample Competency: Networking and Relationships
Keywords: Leadership; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Motivational